Gambaran Pengetahuan, Sikap dan Perilaku Orang Tua dalam Pemanfaatan Buku KIA - Dhea Evita Sari; Nopi Nur Khasanah; Herry Susanto (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
The Maternal and Child Health Book (MCH Book) is an important tool in supporting maternal and child health, including to monitor optimal child development. However, the utilization of the MCH Book is still not optimal in the community, with many parents not utilizing the information in it. This study aims to describe the level of knowledge, attitudes, and behavior of parents in utilizing the MCH Book. This study used a quantitative descriptive design with a cross-sectional approach. A sample of 139 respondents was selected using purposive sampling method at Posyandu Sumurgede Village. Data were collected through a structured questionnaire that measured the level of knowledge, attitude, and behavior of parents towards the utilization of the MCH Book. Data were analyzed univariately to describe the frequency distribution of variables. The results showed that parents' knowledge about MCH Book was mostly good (89.9%), the attitude was predominantly positive (84.2%), and the behavior of MCH Book utilization was mostly good (81.3%). However, there were still respondents with moderate knowledge (10.1%), moderate attitude (12.2%), and moderate behavior (15.1%). Therefore, further educational efforts are needed to increase awareness and more optimal utilization of the MCH Book.